An agent-based simulation of Tsunami evacuation for disaster management: a case study of Khao Lak, Thailand - Nattapon Trumikaborworn; Pennung Warnitchai; Pal, Indrajit; Dailey, Mathew N.; Royal Thai Government; Asian Institute of Technology Fellowship (Pathumthani : Asian Institute of Technology, 2017)
In Thailand, evaluation and implementation of existing tsunami evacuation measures are currently and mainly derived from tabletop exercises and evacuation drills. This paper aims to prepare and demonstrate an agent-based simulation namely TUNAMI -EVAC1 developed by Assoc. Prof. Erick Mas as the alternative method to support the evaluation and implementation process. The model includes spatial information and human evacuation behaviors to represent the process of tsunami evacuation. Moreover, the uncertainty of the model inputs is taken into consideration by the logic-tree framework. We selected two study areas in Khao Lak, Thailand, to investigate how different characteristics of each area impact on the results. Finally, the estimated casualties from the two study areas, and sensitive parameters, are calculated. Approximately, 15% of the population in Bang Niang and 25% in Tab Lamu may not evacuate to the safe zone under current conditions and assumptions used in the model against a tsunami arrival time similar to the one in 2004. Also, the most sensitive parameter is the warning time, followed by the preparation time, and shelter recognition. Therefore, specific recommendations for each area can be incorporated to grasp a clear image of the needs of tsunami evacuation measures in the future.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in disaster Preparedness, Mitigation and Management, School of Environment, Resources and Development {u2013} School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 2017
Keywords: Tsunamis -- Thailand -- Kao Lak; Disaster -- Management -- Thailand -- Kao Lak